(untitled) (Journal of the College of Basic Education, 2025)
The aim of the study is to identify the effectiveness of the Five Pillars Model in metacognitive thinking among second-grade intermediate female students in the subject of chemistry. The researchers employed a quasi-experimental design with two equivalent groups. The research sample was purposively selected from second-grade intermediate students at (Raya Al-Huda Intermediate School for Girls), affiliated with the General Directorate of Education in Babylon Governorate / Center. The total number of students in the research sample was 67, with 34 students in the experimental group, which was taught according to the Five Pillars Model, and 33 students in the control group, which was taught using the traditional method. The researchers conducted statistical equivalence between the two research groups in the variables of previous achievement scores in chemistry, Raven’s intelligence test, prior knowledge test, and the metacognitive thinking scale. The instructional material consisted of Chapter One: Elements and Chemical Bonding, Chapter Two: Chemical Compounds, and Chapter Three: Chemical Formulas and Reactions, which were part of the curriculum for the academic year 2024–2025. The researchers formulated 143 behavioral objectives and prepared the research instrument represented by the metacognitive thinking scale, which consisted of three domains, each containing 10 items. Face validity was obtained by presenting the scale to a group of experts in education, science teaching methods, and psychology. The discriminative power and difficulty index for each item were calculated using appropriate statistical methods, and the reliability was determined using Cronbach’s alpha method, which reached 0.931. After the researchers completed the application of the experiment, the instrument was administered to both research groups, and the students’ responses were scored and statistically processed using the SPSS 24 statistical package. The results showed that the experimental group outperformed the control group, and in light of these results, the researchers presented a number of recommendations and suggestions.